The Practice of al-Ta'awun in the Wedding Expenditure of Malay-Muslims in Malaysia. - Husin, Syh Noorul Madihah Syed; Azahari, Raihanah; Ab Rahman, Asmak (Pertanika Journal of Social Sciences & Humanities, 2020)
Al-ta'awun is a concept regarding mutual help and cooperation in Islam, which is advocated in the al-Quran and Sunnah. Its role in defraying wedding expenditure is seen as a solution to the huge budget incurred when preparing for a wedding reception. Contemporary societies are increasingly faced with the burden of costly weddings, and this can have adverse effects, especially on the Malay-Muslim community in Malaysia. This study examined the application of al-ta'awun to supplement wedding expenses. This qualitative study involved 30 married couples, who were selected for face-to-face interviews comprising semi-structured interviews. The results were arranged and analysed according to themes relevant to this study. Data were examined, coded and categorised based on emerging themes. The ATLAS.ti version 7.5.6 software was used for analysing data, which involved five steps, namely transcription, compilation, coding, categorisation and drawing inferences. The findings indicate that three forms of al-ta'awun are practised, namely monetary donations, payment for goods and services, and contributions to defray the cost of wedding arrangements. The involvement of family, neighbours, friends and the local community helps to defray the overall wedding expenses.